Fundamental Review to Ozone Gas Sensing Using Optical Fibre Sensors - Michael David; Mohd Haniff Ibrahim; Sevia Mahdaliza Idrus; Tay Ching En Marcus (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The manuscript is a review of basic essentials to ozone gas sensing with optical methods. Optical methods are employed to monitor optical absorption, emission, reflectance and scattering of gas samples at specific wavelengths of light spectrum. In the light of their importance in numerous disciplines in analytical sciences, necessary integral information that serves both as a basis and reference material for intending researchers and others in the field is inevitable. This review provides insight into necessary essentials to gas sensing with optical fibre sensors. Ozone gas is chosen as a reference gas. Simulation results for ozone gas absorption cross section in the ultraviolet (UV) region of the spectrum using spectralcalc.com simulation have also been included.